2018
DOI: 10.1007/s00432-018-2732-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of hyperdiploidy in multiple myeloma patients with high-risk cytogenetics: a pilot study in China

Abstract: These results suggest that the coexistence of hyperdiploidy may ameliorate the adverse prognosis of multiple myeloma patients with high-risk cytogenetics. High-risk cytogenetics patients without hyperdiploidy showed the worst prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
2
11
1
Order By: Relevance
“…The median follow-up period was 25 months (IQR: . The median age at diagnosis was 57 years (IQR: 51-64), which was similar to other recent studies of Chinese MM patients (19)(20)(21)(22). According to ISS, 57% (70/123) patients were at stage III.…”
Section: Patient Characteristicssupporting
confidence: 87%
“…The median follow-up period was 25 months (IQR: . The median age at diagnosis was 57 years (IQR: 51-64), which was similar to other recent studies of Chinese MM patients (19)(20)(21)(22). According to ISS, 57% (70/123) patients were at stage III.…”
Section: Patient Characteristicssupporting
confidence: 87%
“…Overall, hyperdiploidy seems to confer a neutral or inferior outcome in AL patients, which is contradictory to results from MM studies that indicate a favorable prognostic effect of hyperdiploidy [ 12 , 13 , 60 ]. The transferability of the classically defined hyperdiploidy in the iFISH method, previously used in MM, to AL remains uncertain, and further studies are needed to define and validate the criteria of hyperdiploidy in AL based on the iFISH method.…”
Section: Hyperdiploidycontrasting
confidence: 71%
“…Several studies have shown that hyperdiploid patients have better response rates to treatment and longer survival than patients with other aneuploidies [87]. This favorable prognosis was observed irrespective of the therapeutic context [88][89][90]. However, not all trisomies have the same impact on survival; in particular, trisomies of chromosomes 3 and 5 improve the prognosis in patients treated with chemotherapy or bortezomib followed by ASCT, and also in those treated with non-intensive protocols, even in patients with t(4;14) [91].…”
Section: Prognosismentioning
confidence: 98%